2017
DOI: 10.4149/bll_2016_131
|View full text |Cite
|
Sign up to set email alerts
|

Is fertility sparing surgery a treatment option for premenopausal patients with dysgerminoma?

Abstract: Dysgerminoma is the most common ovarian germ cell type ovarian tumour. Primarily, it presents in young women at reproductive age and thus, the preservation of fertility is considered to be fundamental when it is possible for these patients. In comparison to the past the restriction of the extent of the surgical procedure as well as the introduction of innovative chemotherapeutic regimens improved signifi cantly both, the prognosis and the clinical outcomes of this rare neoplasia. As dysgerminomas are extremely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…They primarily manifest in young and adolescent women with excellent prognosis if diagnosed in earlier stages [110]. These tumors are chemosensitive allowing fertility-sparing surgery in most cases [111]. A recent small cohort study reported a low mutational burden in OGCTs explaining their chemosensitive disposition [112].…”
Section: Ovarian Germ Cell Tumors (Ogcts)mentioning
confidence: 99%
“…They primarily manifest in young and adolescent women with excellent prognosis if diagnosed in earlier stages [110]. These tumors are chemosensitive allowing fertility-sparing surgery in most cases [111]. A recent small cohort study reported a low mutational burden in OGCTs explaining their chemosensitive disposition [112].…”
Section: Ovarian Germ Cell Tumors (Ogcts)mentioning
confidence: 99%
“…In Mexico, ovarian germ-cell tumors may represent up to 19% of total ovarian malignancies, with up to 59% diagnosed as dysgerminomas 5. Since dysgerminomas are more common in women of reproductive age, the standard treatment for dysgerminomas confined to the ovary is unilateral salpingo-oophorectomy to preserve fertility, followed by chemotherapy 6 7. Most patients with stage IA dysgerminoma are not treated with chemotherapy after the initial surgery, and tend to respond well to chemotherapy if relapse occurs 8.…”
Section: Introductionmentioning
confidence: 99%